PENINGKATAN KETAHANAN KELUARGA DALAM MENGHADAPI PANDEMI COVID-19 MELALUI BUDIDAYA TANAMAN OBAT - Pamungkas, Puguh Bintang; Purwaningsih, Okti; Triwahana, Triwahana (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The Covid-19 pandemic is affecting everyone, especially for the economy. One of the efforts to reduce the burden on the community is to increase the community's independence in drug procurement through the cultivation of family medicinal plants. Community service aims to provide motivation, guidance, and assistance in the cultivation of medicinal plants to increase community resilience in the face of the covid-19 pandemic. The method used in this service is in the form of counseling, group discussion forums and making demonstration plots. The result of this service is KWT Mandan, Banyurejo, Tempel, Sleman DIY motivated for the cultivation of medicinal plants, the realization of a medicinal plant garden.